2015
DOI: 10.14814/phy2.12266
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pigment epithelium-derived factor and thrombospondin-1 regulate proliferation and migration of retinal pigment epithelial cells

Abstract: Age‐related macular degeneration (AMD) is the leading cause of vision loss among elderly. Although the pathogenesis of AMD is associated with retinal pigmented epithelium (RPE) dysfunction and abnormal neovascularization the detailed mechanisms remain unresolved. RPE is a specialized monolayer of epithelial cells with important functions in ocular homeostasis. Pathological RPE damage contributes to major ocular conditions including retinal degeneration and irreversible loss of vision in AMD. RPE cells also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 74 publications
(95 reference statements)
2
29
1
Order By: Relevance
“…These results are in contrast to results obtained in lung endothelial cells and retinal pigment epithelial cells in which cell proliferation was increased in TSP1 −/− and CD47 −/− mice (Farnoodian et al, 2015; Kaur et al, 2013). Thus the effects of TSP1 appear to be tissue specific.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in contrast to results obtained in lung endothelial cells and retinal pigment epithelial cells in which cell proliferation was increased in TSP1 −/− and CD47 −/− mice (Farnoodian et al, 2015; Kaur et al, 2013). Thus the effects of TSP1 appear to be tissue specific.…”
Section: Discussioncontrasting
confidence: 99%
“…PEDF inhibits apoptosis induced by oxidative stress in retinal pericytes preventing their dysfunction [102]. We showed elevated oxidative stress levels in the Serpinf1 −/− RPE cells [73] and choroidal and retinal EC (Our unpublished data). Cao and associates showed that pretreatment of retinal cultures with PEDF inhibited mitochondrial signal transduction and induced apoptosis when challenged with H 2 O 2 [82].…”
Section: Pigment Epithelium Derived Factor (Pedf)mentioning
confidence: 92%
“…Furthermore, the expression of TSP2 was increased in Thbs1 -deficient ChEC [50]. RPE cells also expressed a low amount of TSP2, which was increased in Thbs1 -deficient RPE cells [73]. However, the cell autonomous impact of TSP2 expression on choroidal EC and RPE cell functions remain a subject of future investigation.…”
Section: Amd and Endogenous Inhibitors Of Angiogensismentioning
confidence: 99%
See 2 more Smart Citations